Strong base for fuzzy topology - Zakirov, F. M.; Rakhimov, A. A. (Methods of Functional Analysis and Topology, 2011)
It is known that a base for a traditional topology, or for a L-topology, τ, is a subset B of τ with the property that every element Gτ can be written as a union of elements of B. In the classical case it is equivalent to say that Gτ if and only if for any xG we have BB satisfying xB G. This latter property is taken as the foundation for a notion of strong base for a L-topology. Characteristic properties of a strong base are given and among other results it is shown that a strong base is a base, but not conversely.